The role of national task force in responding to illegal activities during covid-19 pandemic - Tharishini Krishnan; Salma Yusof; Herlin Anak Aman; Kdr Sugenderan Nagalan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Border security is an essential component of Malaysia’s defence and security policy. During the COVID-19 outbreak, Malaysia’s border security management was tested with the increase of illegal entry into the country. The central argument of this paper is that, whilst Movement Control Order (MCO), or lockdown as it is more commonly known, aims to restrict movement, this limited movement was exploited for illegal entries into the country, leading to the establishment of the National Task Force (NTF), which coordinated various enforcement agencies to safeguard Malaysian territory. On this ground, this paper aims to analyse the role of the NTF in responding to increasing illegal activities amidst the pandemic. The discussion is divided into: (a) identifying illegal entries during the pandemic; (b) the impact of illegal entries to border management in Malaysia; (c) examining the roles of the NTF in responding to the illegal activities; and (d) the impact of the NTF in border security management in Malaysia. As a preliminary study, this paper only uses secondary data collection in addressing the problem statement.